TANTANGAN GURU DALAM PEMBELAJARAN SEJARAH PADA MASA PANDEMI COVID-19 DI SMAN 1 WAY SERDANG KABUPATEN MESUJI TAHUN 2021 - Andi Susanto; Umi Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The problem describes the challenges of teachers in learning history during the Covid-19 pandemic at SMAN 1 Way Serdang. Objectives, Describe the challenges faced by teachers and students, the media used by history subject teachers, students' responses to the media used in history lessons and, the efforts of teachers and students in history subjects in facing learning challenges during the covid pandemic. -19 at SMA Negeri 1 Way Serdang Kab Mesuji in 2021. The research uses qualitative methods. With interview data collection techniques, observation, documentation and data analysis techniques. The results of the study, (1) Studying from home is a step taken by the government to stop the spread of Covid-19. Areas that lack public facilities, among others, regarding signals and networks are a challenge for teachers and students, 2) Online learning requires media. In the online learning process at SMAN 1 Way Serdang in learning history using the whatsapp and google classroom application, 3) The response of students using whatsapp and google classroom media is not optimal because the material presented is not accompanied by a direct explanation by the teacher, 4) Obstacles during learning the most important thing is the internet network in the area where students live which is less stable, the efforts made by the teacher to tolerate students who are late in collecting assignments, choosing the right media in online learning. Then the efforts of students to manage online learning by means of students doing the task first if it feels the signal is stable, the task is collected, then adding learning resources from books and the internet to make it easier to understand material that they do not understand.